Agenda regionalnych polityk publicznych oraz opinia publiczna i media w województwie lubelskim. Analiza agenda-setting - Nowak, Ewa (Polityka i Społeczeństwo, 2021)
In the proposed study consideration is given to the problem of the interdependency and distinction of priorities of public opinion, news media and public policies on the local level. The theoretical and methodological basis of the paper consists of the agenda-setting and political responsiveness approaches. The empirical data is divided into three agendas: public, media and policy, which were analysed using comparative statistical analysis. The conclusions pointed at the substantial distinction of the priorities formulated by public opinion and the policies implemented by local government and, to a certain extent, at the interdependency between the news media and local public policy agenda.